Preparation method of porous anode layer structure and structure thereof, fuel cell
By determining the assembly ratio of the anode powder layer and forming a gradient layer structure with ultrasonic spraying technology, the problems of long preparation period and high cost of porous anode layer are solved, and efficient fuel cell preparation and electrode performance improvement are achieved.
Patent Information
- Application Number
- CN202210427083.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-22
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-04-22
AI Technical Summary
The preparation method of the existing porous anode layer requires different solution ratios for different porosities of each layer, resulting in a long preparation cycle, high cost and low efficiency.
By determining the ratio of the first component to the second component of the anode powder layer, the mixed slurry is sprayed on the substrate by ultrasonic spraying technology to form a gradient layer structure, and a porous anode layer is obtained by sintering, which simplifies the Solution configuration process.
It effectively shortens the research and development and preparation cycle of fuel cells, reduces the preparation cost, improves the production efficiency of the porous anode layer structure, and improves the electrode catalytic performance and the combination effect of the electrolyte layer.
Smart Images

Figure CN114824313B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a preparation method of a porous anode layer structure and a structure thereof, and a fuel cell. Background Art
[0002] Anode-supported solid oxide fuel cells are also called ceramic fuel cells. Their key components, porous anode, dense electrolyte, and porous cathode, are all ceramic oxide materials. The porous anode is mainly composed of a mixture of nickel oxide and zirconium oxide, the dense electrolyte is composed of zirconium oxide, and the porous cathode is composed of La. 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3 (LSCF) composite material, in which the porous anode is reduced to nickel and zirconium oxide in a reducing atmosphere and high temperature, thus having catalytic and conductive effects. In this process, as nickel oxide is converted into nickel, its structure changes and the pores become larger. Therefore, the porous anode, as a structural support and gas catalysis and electrode conductive site, has a great influence on battery performance. It is required to have a certain support strength, and at the same time, it must maintain a large number of pores to increase the gas mass transfer rate and reduce the internal resistance. It is also required to be able to maintain a close bond with the electrolyte under long-term high temperature and high humidity operating environment.
[0003] In the related art, the traditional preparation method of porous anodes is mainly for porous anode layers with different porosities. It is necessary to prepare solutions with different proportions in advance, which leads to a long preparation cycle, high preparation cost and low production efficiency. Summary of the invention
[0004] The main purpose of the present invention is to provide a method for preparing a porous anode layer structure, a structure thereof, and a fuel cell, aiming to solve the technical problems of long preparation cycle and high preparation cost leading to low preparation efficiency in related technologies.
[0005] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a porous anode layer structure, comprising the following steps:
[0006] Determining the ratio of the first component to the second component of the current anode powder layer;
[0007] Extracting a first preset amount of a first slurry from a first suspension according to the ratio, and extracting a second preset amount of a second slurry from a second suspension; wherein the first suspension having a target viscosity includes the first component, and the second suspension having the target viscosity includes the second component;
[0008] Mixing the first slurry with the second slurry to obtain a mixed slurry;
[0009] The mixed slurry is sprayed on the substrate by ultrasonic spraying to form a current anode powder layer;
[0010] The current anode powder layer to be formed adjacent to the current anode powder layer is used as the current anode powder layer, and the step of determining the ratio of the first component to the second component of the current anode powder layer is returned to execute until the number of layers of the current anode powder layer reaches a preset number of layers to obtain an anode gradient layer structure;
[0011] The anode gradient layer structure with the preset number of layers is sintered to obtain a porous anode layer structure.
[0012] Optionally, before the step of determining the ratio of the first component to the second component of the current anode powder layer, the step includes:
[0013] Adding nickel oxide powder and graphite powder having a preset average particle size into an anhydrous ethanol solvent to obtain a nickel oxide-graphite suspension, and adding zirconium oxide powder having the preset average particle size into an anhydrous ethanol solvent to obtain a zirconium oxide suspension;
[0014] Ball milling the nickel oxide-graphite suspension to obtain a first initial slurry, and ball milling the zirconium oxide suspension to obtain a second initial slurry;
[0015] Adding a dispersant and a binder to both the first initial slurry and the second initial slurry;
[0016] The first initial slurry is ball-milled to obtain the first suspension having a target viscosity, and the second initial slurry is ball-milled to obtain the second suspension having the target viscosity.
[0017] Optionally, the preset average particle size is not higher than 0.5 μm.
[0018] Optionally, the step of ball-milling the nickel oxide-graphite suspension to obtain a corresponding first initial slurry, and ball-milling the zirconium oxide suspension to obtain a second initial slurry comprises:
[0019] The nickel oxide-graphite suspension is ball-milled and mixed according to the target time to obtain a corresponding first initial slurry, and the zirconium oxide suspension is ball-milled and mixed according to the target time to obtain a second initial slurry, wherein the target time is not less than 8 hours.
[0020] Optionally, the step of ball-milling the first initial slurry to obtain the first suspension having a target viscosity, and ball-milling the second initial slurry to obtain the second suspension having the target viscosity comprises:
[0021] The first initial slurry is ball-milled and mixed according to the target time to obtain the first suspension having the target viscosity, and the second initial slurry is ball-milled and mixed according to the target time to obtain the second suspension having the target viscosity.
[0022] Optionally, the target viscosity is no higher than 100 cps.
[0023] Optionally, the step of spraying the mixed slurry onto the substrate by ultrasonic spraying to form the current anode powder layer comprises:
[0024] The mixed slurry is sprayed on the substrate by ultrasonic spraying to obtain a single-layer anode slurry layer;
[0025] The single-layer anode slurry layer is dried at the target temperature to obtain the current anode powder layer.
[0026] Optionally, before the step of mixing the first slurry with the second slurry to obtain a mixed slurry, the step includes:
[0027] The first slurry and the second slurry are dispersed respectively by ultrasonic dispersion.
[0028] Based on the same inventive concept, in a second aspect, the present invention proposes a porous anode layer structure, which is prepared by the preparation method described in the first aspect.
[0029] Based on the same inventive concept, in a third aspect, the present invention provides a fuel cell, comprising the porous anode layer structure described in the second aspect.
[0030] The technical solution of the present invention first determines the ratio of the first component and the second component of the current anode powder layer, then extracts a first preset amount of the first slurry from the first suspension with a target viscosity according to the determined ratio, and extracts a second preset amount of the second slurry from the second suspension with the same target viscosity as the first suspension, and then disperses the mixture formed by the first slurry and the second slurry to obtain a mixed slurry, and then sprays the mixture on the substrate by ultrasonic spraying to form the current anode powder layer, and then uses the current anode powder layer to be formed adjacent to the current anode powder layer as the current anode powder layer, and returns to determine the ratio of the first component and the second component of the current anode powder layer until the number of layers of the current anode powder layer reaches the preset number of layers, and obtains the anode gradient layer structure. Two basic solutions are first separately configured, and then according to the ratio required for each porous anode layer, the first suspension of the first component is directly extracted and mixed in the second suspension with the second component directly extracted, and then the nickel oxide and zirconium oxide anode powder gradient layer with any percentage content is prepared. Unlike the related art, it is no longer necessary to separately prepare a solution of corresponding proportion for each porous anode layer. This solves the technical defects of the related art that the slurry needs to be separately prepared in order to prepare different porous anode layers, which causes complicated process and time-consuming and labor-intensive process. It effectively shortens the research and development and preparation cycle of fuel cells, reduces the preparation cost, and improves the production efficiency of the porous anode layer structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0032] Figure 1 Schematic diagram of the process of preparing the porous anode layer structure of the present invention;
[0033] Figure 2 for Figure 1 Schematic diagram of the process of the steps before step S100;
[0034] Figure 3 A schematic diagram of the structure of a porous anode layer according to an embodiment of the present invention.
[0035] Description of Figure Numbers:
[0036] Label name Label name 100 substrate 200 Porous structure layer
[0037] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0040] In the present invention, unless otherwise clearly specified and limited, the terms "connection", "fixation", etc. should be understood in a broad sense. For example, "fixation" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0041] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes. Taking "A and / or B" as an example, it includes scheme A, or scheme B, or a scheme that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0042] Anode-supported solid oxide fuel cells are also called ceramic fuel cells. Their key components, porous anode, dense electrolyte, and porous cathode, are all ceramic oxide materials. The porous anode is mainly composed of a mixture of nickel oxide and zirconium oxide, the dense electrolyte is composed of zirconium oxide, and the porous cathode is composed of La. 0.6 Sr0.4 Co 0.2 Fe 0.8 O3 (LSCF) composite material, in which the porous anode is reduced to nickel and zirconium oxide in a reducing atmosphere and high temperature, thus having catalytic and conductive effects. In this process, as nickel oxide is converted into nickel, its structure changes and the pores become larger. Therefore, the porous anode, as a structural support and gas catalysis and electrode conductive site, has a great influence on battery performance. It is required to have a certain support strength, and at the same time, it must maintain a large number of pores to increase the gas mass transfer rate and reduce the internal resistance. It is also required to be able to maintain a close bond with the electrolyte under long-term high temperature and high humidity operating environment.
[0043] In the related art, the traditional preparation method of porous anodes is mainly for porous anode layers with different porosities. It is necessary to prepare solutions with different proportions in advance, which leads to a long preparation cycle, high preparation cost and low production efficiency.
[0044] Therefore, the present invention proposes a method for preparing a porous anode layer 200 structure, a structure thereof, and a fuel cell.
[0045] The inventive concept of the present invention is further described below in conjunction with some specific implementation methods.
[0046] In one embodiment, if Figure 1 As shown, the porous anode layer 200 structure comprises the following steps:
[0047] S100, determining a ratio of a first component to a second component of a current anode powder layer;
[0048] In this embodiment, the method for determining the ratio of the first component and the second component of the current anode powder layer is mainly determined according to the porosity of the current anode powder layer. In actual operation, each layer of the current anode powder layer has a corresponding ratio. Of course, the ratio can also be determined according to the model of the fuel cell, which will not be described in detail here. However, it can be further clarified that in actual operation, the number of layers of the current anode powder layer and the porosity of each layer of the current anode powder layer can be determined according to the model of the fuel cell.
[0049] S200, extracting a first preset amount of a first slurry from the first suspension according to a ratio, and extracting a second preset amount of a second slurry from the second suspension; wherein the first suspension having a target viscosity includes a first component, and the second suspension having a target viscosity includes a second component;
[0050] In this embodiment, after determining the ratio of the current anode powder layer, a micro-injection pump is controlled to extract a first preset amount of a first slurry from a first suspension having a target viscosity, and then another micro-grouting pump is controlled to extract a second preset amount of a second slurry from a second suspension having the same target viscosity as the first suspension. It should be emphasized that the first suspension includes a first component and the second suspension includes a second component.
[0051] It should be clarified and explained that the target viscosities of the first suspension and the second suspension exemplified in this embodiment may be the same or different. Specifically, they may be adaptively configured according to the base material and base solvent of the configured first suspension. Of course, it should be further clarified that the base materials of the first suspension and the second suspension may be the same or different. In actual application, they may be determined according to the model and type of the fuel cell. However, it should be clarified that the solvents used in the first suspension and the second suspension exemplified in this embodiment must be the same, so as to ensure that no chemical reaction occurs after the first suspension and the second suspension are mixed.
[0052] S300, mixing the first slurry and the second slurry to obtain a mixed slurry;
[0053] The micro-injection pump illustrated in this embodiment mainly adopts the existing micro-injection pump. This embodiment only applies it and does not improve or design the structure of the micro-injection pump itself. Therefore, its working principle and specific structure will not be described one by one.
[0054] S400, spraying the mixed slurry onto the substrate 100 by ultrasonic spraying to form a current anode powder layer;
[0055] In this embodiment, after the first suspension and the second suspension are mixed and a mixed slurry is obtained, the mixed slurry is sprayed onto the substrate 100 using an ultrasonic nozzle to obtain a current anode powder layer.
[0056] It should be noted that, in this embodiment, when the current anode powder layer is produced, spraying may be performed according to the structure and thickness of the anode layer corresponding to the current anode powder layer. In addition, the ultrasonic nozzle used in this embodiment mainly adopts the existing ultrasonic nozzle, and this embodiment only applies it without improving or designing the structure of the ultrasonic nozzle itself, so its working principle and specific structure will not be described one by one.
[0057] S500, taking the current anode powder layer to be formed adjacent to the current anode powder layer as the current anode powder layer, and returning to determine the ratio of the first component to the second component of the current anode powder layer, until the number of layers of the current anode powder layer reaches a preset number of layers, thereby obtaining an anode gradient layer structure;
[0058] In this embodiment, after the production of the current anode powder layer is completed, the current anode powder layer to be formed is used as the current anode powder layer, and then the first component and the second component of the current anode powder layer are determined again until the number of layers of the current anode powder layer reaches the preset number of layers, thereby obtaining the anode gradient layer structure. Through the process illustrated in this embodiment, the present invention only needs to follow up the corresponding ratio required by the current anode powder layer to configure the mixed slurry when producing the anode gradient layer, thereby eliminating the technical defect of the related art that the slurry needs to be configured separately when preparing each porous anode layer 200, thereby reducing the production time and improving the production efficiency.
[0059] Of course, it should be particularly and clearly stated that, in this embodiment, the preset number of layers in the example can be determined according to the number of gradient layers required by the specific model of the fuel cell.
[0060] S600, sintering a preset number of anode gradient layer structures to obtain a porous anode layer 200 structure.
[0061] In this embodiment, after the anode gradient layer is manufactured, the anode gradient layer is sintered so that the anode gradient layer forms a porous anode layer 200 structure.
[0062] In this embodiment, it can be further explained that when the anode gradient layer is sintered, it can be sintered by laser sintering but is not limited to it. Of course, in this embodiment, only the manufacturing method of the porous anode gradient layer structure is exemplified.
[0063] The technical solution of the present invention first determines the ratio of the first component to the second component of the current anode powder layer, then extracts a first preset amount of the first slurry from a first suspension having a target viscosity according to the determined ratio, and extracts a second preset amount of the second slurry from a second suspension having the same target viscosity as the first suspension, and then disperses the mixture formed by the first slurry and the second slurry to obtain a mixed slurry, and then sprays the mixture on a substrate by ultrasonic spraying to form the current anode powder layer, and then uses the current anode powder layer to be formed adjacent to the current anode powder layer as the current anode powder layer, and returns to determine the ratio of the first component to the second component of the current anode powder layer, until the current anode powder layer is When the number of layers reaches a preset number, an anode gradient layer structure is obtained. Two basic solutions are first separately prepared, and then according to the required ratio of each porous anode layer, a first suspension of the first component is directly extracted and mixed with a second suspension of the second component that is directly extracted, so as to prepare a gradient layer of nickel oxide and zirconium oxide anode powders with any percentage content. Unlike the related art, it is no longer necessary to separately prepare a solution of corresponding ratio for each porous anode layer. This solves the technical defects of the related art that the slurry needs to be separately prepared in order to prepare different porous anode layers, which causes a complex process and is time-consuming and labor-intensive. It effectively shortens the research and development and preparation cycle of fuel cells, reduces the preparation cost, and improves the production efficiency of the porous anode layer structure.
[0064] In some specific embodiments, Figure 2 As shown, before the step of determining the ratio of the first component to the second component of the current anode powder layer, the method includes:
[0065] A100, adding nickel oxide powder and graphite powder having a preset average particle size into an anhydrous ethanol solvent to obtain a nickel oxide-graphite suspension, and adding zirconium oxide powder having a preset average particle size into an anhydrous ethanol solvent to obtain a zirconium oxide suspension;
[0066] When preparing the nickel oxide-graphite suspension, the ratio of nickel oxide powder to graphite powder is first determined. Of course, in actual implementation, the mass ratio or weight ratio of nickel oxide powder to graphite powder can be any ratio. In this embodiment, the preferred ratio is 1:1.
[0067] It should be particularly and clearly stated that the preset average particle size exemplified in this embodiment can be determined according to the average particle size requirements of ultrasonic atomization and fuel cell materials, and the exemplary preset average particle size is generally not higher than 0.5 μm.
[0068] A200, ball-milling the nickel oxide-graphite suspension to obtain a first initial slurry, and ball-milling the zirconium oxide suspension to obtain a second initial slurry;
[0069] In this embodiment, when the nickel oxide-graphite suspension and the zirconium oxide suspension are respectively ball-milled and mixed, the ball-milling mixing time of the two solutions can be the same ball-milling time or different ball-milling mixing times. The specific ball-milling mixing time depends on the total amount of the nickel oxide-graphite suspension configured at that time and the total amount of the zirconium oxide suspension configured at that time.
[0070] A300, adding a dispersant and a binder to both the first initial slurry and the second initial slurry;
[0071] In this embodiment, the total amount of dispersant and binder added to the first initial slurry and the second initial slurry can be the same or different, and the specific total amount added depends on the total amount of nickel oxide-graphite suspension configured at that time and the total amount of zirconium oxide suspension configured at that time.
[0072] It should be particularly and clearly stated that, in this embodiment, the dispersant used as an example is mainly PVP, and the binder used as an example is mainly PVA.
[0073] A400, ball milling the first initial slurry to obtain a first suspension having a target viscosity, and ball milling the second initial slurry to obtain a second suspension having a target viscosity.
[0074] In this embodiment, before the first initial slurry and the second initial slurry are respectively ball-milled and mixed, the target viscosity that the first initial slurry and the second initial slurry need to reach needs to be determined. Of course, the target viscosities of the two suspensions illustrated in this embodiment can be the same or different. The target viscosity illustrated in this embodiment can be determined according to the specific model of the fuel cell, and the exemplary target viscosity is generally not higher than 100 cps.
[0075] In some specific embodiments, Figure 2 As shown, the steps of ball-milling the nickel oxide-graphite suspension to obtain the corresponding first initial slurry, and ball-milling the zirconium oxide suspension to obtain the second initial slurry include:
[0076] The nickel oxide-graphite suspension is ball-milled and mixed according to the target time to obtain a first initial slurry, and the zirconium oxide suspension is ball-milled and mixed according to the target time to obtain a second initial slurry, wherein the target time is not less than 8 hours.
[0077] In this embodiment, the planetary ball milling equipment is mainly used to respectively ball mill and mix the nickel oxide-graphite suspension and the zirconium oxide suspension. The ball milling mixing time is generally not less than 8 hours, and the specific ball milling mixing time can be determined according to the specific model of the fuel cell.
[0078] In some specific embodiments, Figure 2 As shown, the steps of ball milling the first initial slurry to obtain a first suspension having a target viscosity, and ball milling the second initial slurry to obtain a second suspension having a target viscosity include:
[0079] The first initial slurry is ball-milled and mixed according to the target time to obtain a first suspension having a target viscosity, and the second initial slurry is ball-milled and mixed according to the target time to obtain a second suspension having a target viscosity.
[0080] In this embodiment, a planetary ball mill is mainly used to respectively mill and mix the first initial slurry and the second initial slurry. The mixing time of the ball milling is generally not less than 8 hours, and the specific ball milling mixing time can be determined according to the specific model of the fuel cell.
[0081] In some specific embodiments, Figure 2 As shown, the steps of spraying the mixed slurry onto the substrate 100 by ultrasonic spraying to form the current anode powder layer include:
[0082] S401, spraying the mixed slurry onto the substrate 100 by ultrasonic spraying to obtain a single-layer anode slurry layer;
[0083] In this embodiment, the mixed slurry is mainly sprayed onto the substrate 100 using an ultrasonic nozzle, and the thickness of each single anode slurry layer can be determined according to the specific model of the fuel cell.
[0084] Of course, it needs to be specially and clearly stated that, in this embodiment, the example substrate 100 is mainly a plate structure or a column structure made of relevant materials with corrosion resistance, such as a ceramic plate, etc. In this embodiment, a metal plate is mainly used as the substrate 100.
[0085] S402, drying the single-layer anode slurry layer at the target temperature to obtain a current anode powder layer.
[0086] In this embodiment, the anhydrous ethanol solvent of the single-layer anode slurry layer is completely evaporated in an atmosphere of a temperature of 150° C., thus completing the drying.
[0087] Optionally, before dispersing the mixture formed by the first slurry and the second slurry to obtain the mixed slurry, the step includes:
[0088] The first slurry and the second slurry are dispersed respectively by ultrasonic dispersion.
[0089] In this embodiment, a 40K 100W ultrasonic dispersion device is mainly used to fully disperse the slurry to obtain a mixed slurry. In this embodiment, only the ultrasonic dispersion device is applied, and the improvement or design of the structure of the ultrasonic dispersion device itself is not involved, so the specific structure and working principle of the ultrasonic dispersion device are not described one by one here.
[0090] In some specific embodiments, first, nano nickel oxide and zirconium oxide powders with a powder particle size of less than 0.5 μm are selected, and graphite powder is added to the nickel oxide as a pore-forming agent. Anhydrous ethanol is used as a solvent with a mass ratio of 7:3 to the powder. The mixture is first mixed and ball-milled at 360 r / min for 8 hours in a ball mill, and then a trace amount of dispersant PVP and a small amount of binder PVA are added. The mixture is ball-milled at 360 r / min for 8 hours to obtain two slurries of nickel oxide and zirconium oxide, respectively. After sieving and vacuum degassing, the viscosity of the slurry is controlled to be about 30 cps, and the slurry is placed in an ultrasonic dispersion tank to be fully dispersed and kept uniform.
[0091] Then, taking zirconium oxide as the substrate 100, 1 g of nickel oxide slurry and 0 g of zirconium oxide slurry were respectively extracted into two high-precision micro-injection pumps through the control system. The micro-injection pumps accurately controlled the flow rate and mixed them in the mixing zone placed before the ultrasonic atomizing nozzle. The slurry was then evenly sprayed on the substrate 100 through the ultrasonic atomizing nozzle. The spraying moving speed was set to control the spraying thickness of each layer to be 5 μm, and the spraying area was 50*50 mm. The substrate 100 was heated to 150°C by a thermocouple, so that the solvent was completely evaporated when sprayed on the substrate 100, and the first layer was obtained on the substrate 100.
[0092] Afterwards, the remaining slurry in the above-mentioned micro-injection pump and the mixing zone is discharged from the waste barrel, and the second layer is sprayed on the substrate 100. 0.9g of nickel oxide slurry and 0.1g of zirconium oxide slurry are respectively drawn into two high-precision micro-injection pumps through the control system. The micro-injection pumps accurately control the flow rate and mix them in the mixing zone placed before the ultrasonic atomization nozzle. The slurry is then evenly sprayed on the first layer through the ultrasonic atomization nozzle. The substrate 100 is heated to 150°C by a thermocouple to completely evaporate the solvent when sprayed onto the substrate 100, thereby obtaining the second layer on the substrate 100.
[0093] Finally, the spraying is repeated 20 times to obtain a complete anode gradient layer, and the anode gradient layer is sintered at a high temperature to obtain a complete porous anode gradient layer.
[0094] In other specific embodiments, first, nano nickel oxide and zirconium oxide powders with a powder particle size of less than 0.5 μm are selected, graphite powder is added to the nickel oxide as a pore-forming agent, and anhydrous ethanol is used as a solvent with a mass ratio of 1:1 to the powder. The mixture is first mixed and ball-milled at 360 r / min for 8 hours in a ball mill, and then a trace amount of dispersant PVP and a small amount of binder PVA are added, and then ball-milled at 360 r / min for 8 hours to obtain two slurries of nickel oxide and zirconium oxide, respectively. After sieving and vacuum degassing, the viscosity of the slurry is controlled to be about 30 cps, and the slurry is placed in an ultrasonic dispersion tank to be fully dispersed and kept uniform.
[0095] Then, taking zirconium oxide as the substrate 100, 1 g of nickel oxide slurry and 0 g of zirconium oxide slurry were respectively extracted into two high-precision micro-injection pumps through the control system. The micro-injection pumps accurately controlled the flow rate and mixed them in the mixing zone placed before the ultrasonic atomizing nozzle. The slurry was then evenly sprayed on the substrate 100 through the ultrasonic atomizing nozzle. The spraying moving speed was set to control the spraying thickness of each layer to be 5 μm, and the spraying area was 50*50 mm. The substrate 100 was heated to 150°C by a thermocouple, so that the solvent was completely evaporated when sprayed on the substrate 100, and the first layer was obtained on the substrate 100.
[0096] Afterwards, the remaining slurry in the above-mentioned micro-injection pump and the mixing zone is discharged from the waste barrel, and the second layer is sprayed on the substrate 100. 0.9g of nickel oxide slurry and 0.1g of zirconium oxide slurry are respectively drawn into two high-precision micro-injection pumps through the control system. The micro-injection pumps accurately control the flow rate and mix them in the mixing zone placed before the ultrasonic atomization nozzle. The slurry is then evenly sprayed on the first layer through the ultrasonic atomization nozzle. The substrate 100 is heated to 150°C by a thermocouple to completely evaporate the solvent when sprayed onto the substrate 100, thereby obtaining the second layer on the substrate 100.
[0097] Finally, the spraying is repeated 20 times to obtain a complete anode gradient layer, and the anode gradient layer is sintered at a high temperature to obtain a complete porous anode gradient layer.
[0098] In some further specific embodiments, first, nano nickel oxide and zirconium oxide powders with a powder particle size of less than 0.5 μm are selected, graphite powder is added to the nickel oxide as a pore-forming agent, and anhydrous ethanol is used as a solvent with a mass ratio of 7:3 to the powder. The mixture is first mixed and ball-milled at 360 r / min for 8 hours in a ball mill, and then a trace amount of dispersant PVP and a small amount of binder PVA are added, and then ball-milled at 360 r / min for 8 hours to obtain two slurries of nickel oxide and zirconium oxide, respectively. After sieving and vacuum degassing, the viscosity of the slurry is controlled to be about 30 cps, and the slurry is placed in an ultrasonic dispersion tank to be fully dispersed and kept uniform.
[0099] Then, taking zirconium oxide as substrate 100, 1 g of nickel oxide slurry and 0 g of zirconium oxide slurry were respectively extracted into two high-precision micro-injection pumps through the control system. The micro-injection pumps accurately controlled the flow rate and mixed them in the mixing zone placed before the ultrasonic atomizing nozzle. The slurry was then evenly sprayed on the substrate 100 through the ultrasonic atomizing nozzle. The spraying thickness of each layer was controlled to be 1 μm by setting the spraying moving speed, and the spraying area was 50*50 mm. The substrate 100 was heated to 150°C by a thermocouple, so that the solvent was completely evaporated when sprayed on the substrate 100, and the first layer was obtained on the substrate 100.
[0100] Afterwards, the remaining slurry in the above-mentioned micro-injection pump and the mixing zone is discharged from the waste barrel, and the second layer is sprayed on the substrate 100. 0.9g of nickel oxide slurry and 0.1g of zirconium oxide slurry are respectively drawn into two high-precision micro-injection pumps through the control system. The micro-injection pumps accurately control the flow rate and mix them in the mixing zone placed before the ultrasonic atomization nozzle. The slurry is then evenly sprayed on the first layer through the ultrasonic atomization nozzle. The substrate 100 is heated to 150°C by a thermocouple to completely evaporate the solvent when sprayed onto the substrate 100, thereby obtaining the second layer on the substrate 100.
[0101] Finally, the spraying is repeated 100 times to obtain a complete anode gradient layer, and the anode gradient layer is sintered at a high temperature to obtain a complete porous anode gradient layer.
[0102] Based on the same inventive concept, please refer to Figure 3 The present invention proposes a porous anode layer 200 structure, which is prepared by the preparation method exemplified above.
[0103] In this embodiment, a porous anode gradient layer is prepared by the preparation method of the present invention, which reduces the steps of preparing multiple slurries, casting, lamination, and degumming, can effectively shorten the fuel cell research and development, preparation cycle, and reduce the preparation cost. Moreover, anode powder gradient layers with different percentages can be prepared by a micro-injection pump and ultrasonic dispersion spray, thereby improving the electrode catalytic performance and the combination effect with the electrolyte layer, which can effectively promote the application of fuel cells.
[0104] Based on the same inventive concept, the present invention provides a fuel cell, comprising the porous anode layer 200 structure exemplified above.
[0105] In this embodiment, a porous anode gradient layer is prepared by the preparation method of the present invention, which reduces the steps of preparing multiple slurries, casting, lamination, and degumming, can effectively shorten the fuel cell research and development, preparation cycle, and reduce the preparation cost. Moreover, anode powder gradient layers with different percentages can be prepared by a micro-injection pump and ultrasonic dispersion spray, thereby improving the electrode catalytic performance and the combination effect with the electrolyte layer, which can effectively promote the application of fuel cells.
[0106] The above descriptions are only optional embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present invention's specification and drawings, or directly / indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a porous anode layer structure, characterized in that: The steps include: Adding nickel oxide powder and graphite powder having a preset average particle size into an anhydrous ethanol solvent to obtain a nickel oxide-graphite suspension, and adding zirconium oxide powder having the preset average particle size into an anhydrous ethanol solvent to obtain a zirconium oxide suspension; Ball milling the nickel oxide-graphite suspension to obtain a first initial slurry, and ball milling the zirconium oxide suspension to obtain a second initial slurry; Adding a dispersant and a binder to both the first initial slurry and the second initial slurry; Ball milling the first initial slurry to obtain a first suspension having a target viscosity, and ball milling the second initial slurry to obtain a second suspension having the target viscosity; Determine a ratio of a first component to a second component of a current anode powder layer; wherein the first component decreases gradually from the substrate toward a direction away from the substrate, and the second component increases gradually from the substrate toward a direction away from the substrate; Extracting a first preset amount of the first slurry from the first suspension according to the ratio, and extracting a second preset amount of the second slurry from the second suspension; wherein the first suspension having the target viscosity includes the first component, and the second suspension having the target viscosity includes the second component; Mixing the first slurry with the second slurry to obtain a mixed slurry; The mixed slurry is sprayed on the substrate by ultrasonic spraying to form a current anode powder layer; The current anode powder layer to be formed adjacent to the current anode powder layer is used as the current anode powder layer, and the step of determining the ratio of the first component to the second component of the current anode powder layer is returned to execute until the number of layers of the current anode powder layer reaches a preset number of layers, thereby obtaining an anode gradient layer structure; The anode gradient layer structure with the preset number of layers is sintered to obtain a porous anode layer structure.
2. The method for preparing a porous anode layer structure according to claim 1, characterized in that: The preset average particle size is not higher than 0.5 μm.
3. The method for preparing a porous anode layer structure according to claim 1, characterized in that: The step of ball-milling the nickel oxide-graphite suspension to obtain a corresponding first initial slurry, and ball-milling the zirconium oxide suspension to obtain a second initial slurry comprises: The nickel oxide-graphite suspension is ball-milled and mixed according to the target time to obtain a corresponding first initial slurry, and the zirconium oxide suspension is ball-milled and mixed according to the target time to obtain a second initial slurry, wherein the target time is not less than 8 hours.
4. The method for preparing a porous anode layer structure according to claim 3, characterized in that: The step of ball-milling the first initial slurry to obtain the first suspension having a target viscosity, and ball-milling the second initial slurry to obtain the second suspension having the target viscosity comprises: The first initial slurry is ball-milled and mixed according to the target time to obtain the first suspension having the target viscosity, and the second initial slurry is ball-milled and mixed according to the target time to obtain the second suspension having the target viscosity.
5. The method for preparing a porous anode layer structure according to claim 1, characterized in that: The target viscosity is no higher than 100 cps.
6. The method for preparing a porous anode layer structure according to any one of claims 1 to 5, characterized in that: The step of spraying the mixed slurry onto the substrate by ultrasonic spraying to form the current anode powder layer comprises: The mixed slurry is sprayed on the substrate by ultrasonic spraying to obtain a single-layer anode slurry layer; The single-layer anode slurry layer is dried at the target temperature to obtain the current anode powder layer.
7. The method for preparing a porous anode layer structure according to any one of claims 1 to 5, characterized in that: Before the step of mixing the first slurry with the second slurry to obtain a mixed slurry, the method comprises: The first slurry and the second slurry are dispersed respectively by ultrasonic dispersion.
8. A porous anode layer structure, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 7.
9. A fuel cell, characterized in that: Comprising the porous anode layer structure as claimed in claim 8.